EVALUATION OF EFFICIENCY AND SAFETY OF CHEMOTHERAPY FOR PROSTATE TUBERCULOSIS PATIENTS - E. V. Kulchavenya; A. V. Osadchiy (Туберкулез и болезни лёгких)
Open prospective comparative randomized study was conducted in order to evaluate e`ciency and safety of various techniques of administration of rifampycin, anti-tuberculosis drug, into the prostate. 36 patients at the age from 32 to 60 years old (38,9 years old on the average) were randomly selected into three groups, 12 patients in each group. All of them were treated with rifampicin in the dose of 0.6 g on the daily basis. The 1st group took the medication per os, the second group received intravenous injections, and the third group received the medication per rectum for 5 days. The method which less inhibited the quality and quantity of ejaculate was considered the safest. The e`ciency was evaluated by the reduction of pyospermia. The confidence of diwerences was evaluated by criteria of χ 2 (Statistica 6).The most e`cient method of anti-tuberculosis drug administration for prostate tuberculosis patients is the intravenous drip infusion and administration of curative mixture in micro-clysis, the diwerence between these two techniques is insignificant. Per os intake rifampycin is confidently less e`cient compared to intravenous and per rectum administration techniques. The safest method regarding morphology, motility, quantity and concentration of sperms is per os and per rectum administration of rifampicin. Thus the best combination of e`ciency and safety for anti-tuberculosis drugs administration for prostate tuberculosis patients is introduction of curative combination of drugs in micro-clysis.